Endothelial signaling and the dynamic regulation of arterial tone: A surreptitious relationship. (April 2017) - Welsh, Donald G.; Longden, Thomas A.
Abstract: The endothelium is an integrated layer of cells whose dynamic regulation governs arterial tone development and the matching of blood flow delivery to tissue energetic demand. Investigating the structural and electrical properties of native endothelial cells has been a challenging prospect, with efforts often restricted to traditional myographic techniques. Concerted experimental attention, along with recent technical advances, has broadened the investigative tool kit, deepening mechanistic insights. This overview in part of a STI centered on the endothelium and how key structural/electrical properties guide arterial tone development and integrated network behavior. Articles are written in a provocative, opinionated manner to provoke deeper thought and to highlight areas of investigative deficiency.